Animal, Subject, Constitution - De Ville, Jacques (Mosaic (Winnipeg), 2021)
[...]very little, if any, account is taken of ethological and primatological studies by these theorists in their discussion of animals. [...]he raises questions about whether human beings can in fact be said to have the specific characteristic or ability which is attributed to them exclusively, for example, autonomy, responsibility, morality, or having access to death as such. According to Kant in the Anthropology, this is the power to say "I" as well as the ability to enter the "civil condition." According to Kant, human beings share in two worlds: the sensible and the intelligible.